2017
DOI: 10.1080/14737140.2017.1355242
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, alopecia and stomatitis among patients with breast cancer receiving cyclin-dependent kinase 4 and 6 inhibitors: a systematic review and meta-analysis

Abstract: CDK4/6 inhibitors were associated with an increased risk of fatigue, alopecia and stomatitis. Further studies with self-reported questionnaires may elucidate the impact of the increased risk of these selected adverse effects on the patients' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…This suggests that fatigue is quite common and other clinical factors, including the neurophysiological effects of the breast cancer itself, likely contribute to the experience of fatigue rather than the effects of chemotherapy alone. We found that an increase in fatigue was reported during the chemotherapy treatment period, which supported the study hypotheses and was consistent with prior reports of fatigue in the context of chemotherapy . A decrease in fatigue severity, which occurred for most women by 1‐year post‐chemotherapy indicates that chemotherapy did not produce long‐term exacerbation of fatigue beyond the levels experienced prior to chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that fatigue is quite common and other clinical factors, including the neurophysiological effects of the breast cancer itself, likely contribute to the experience of fatigue rather than the effects of chemotherapy alone. We found that an increase in fatigue was reported during the chemotherapy treatment period, which supported the study hypotheses and was consistent with prior reports of fatigue in the context of chemotherapy . A decrease in fatigue severity, which occurred for most women by 1‐year post‐chemotherapy indicates that chemotherapy did not produce long‐term exacerbation of fatigue beyond the levels experienced prior to chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…GI adverse drug reactions are generally well controlled by standard antiemetic (e.g., metoclopramide, serotonin 5-HT3 antagonists), while the prophylactic administration of loperamide is recommended to prevent diarrhea in patient treated with abemaciclib [23]. Fatigue, alopecia and stomatitis have also been reported among patients treated with this class of drugs [24].…”
Section: Safetymentioning
confidence: 99%
“…TypeConditions Likelihood Comorbidities Hypothyroidism, hypothermia, extreme bradycardia, cardiac disorders, kidney failure, liver dysfunction, poorly controlled diabetes Torsade de pointes. References:[24,40,56,57].…”
mentioning
confidence: 99%
“…Oral mucositis, specifically stomatitis characterized by aphthous ulcer, occurs in very few patients treated with cyclin-dependent kinase 4/6 inhibitors (CDK4/6) [50,51], used as first-or second-line treatment for hormone positive/HER2 negative metastatic breast cancer. However, this regimen promotes GIM rather than OM.…”
Section: Mucositis Pathogenesismentioning
confidence: 99%